Robotic arm-assisted vs conventional unicompartmental knee arthroplasty: A meta-analysis of the effects on clinical outcomes. Issue 35 (August 2019) - Zhang, Fengjun; Li, Hongcai; Ba, Zhaochen; Bo, Chunguang; Li, Kai
Abstract: Background: Robotic arm-assisted unicompartmental knee arthroplasty (UKA) has been recommended for treatment of unicompartmental knee osteoarthritis. However, its effectiveness and safeness remain controversial compared with conventional UKA. Therefore, the goal of this study was to perform a meta-analysis to re-evaluate the effects of robotic arm-assisted UKA on clinical functional outcomes. Methods: PubMed, Embase, and Cochrane Library databases were searched to screen the relevant studies. Continuous data (surgical time, knee excursion during weight acceptance, American knee society score [AKSS], Oxford knee score [OKS], forgotten joint score [FJS], visual analog scale [VAS], and range of motion [ROM]) were pooled using a standardized mean difference (SMD) with their corresponding 95% confidence intervals (CIs) to estimate the effect size, while dichotomous data (complication rate, revision rate) were pooled to obtain the relative risk (RR) with a 95% CI by STATA 13.0 software. Results: Eleven studies involving 498 patients undergoing robotic-assisted UKA and 589 patients receiving conventional UKA were included. Our pooled results demonstrated that robotic-assisted could significantly reduce the complication rate (RR: 0.62, 95% CI: 0.45–0.85; P = .0041) and improve the knee excursion during weight acceptance (SMD: 0.62, 95% CI: 0.25–1.00; P = .001), but prolonged the surgical time (SMD: 0.74, 95% CI: 0.40–1.08; P < .001). No significant difference in the revision rate, AKSS, OKS, FJS, VAS, and ROM between robotic-assisted and conventional UKA groups. Conclusion: This meta-analysis demonstrates robotic-assisted UKA may be an effective and safe surgical procedure for treatment of unicompartmental knee osteoarthritis.